Trade Credit Insurance and Asymmetric Information Problem - Sokolovska Olena (Scientific Annals of Economics and Business, 2017)
The presence of different risk factors in international trade gives evidence of the necessity of support in gaps that may affect exporters’ activity. To maximize the trade volumes and in the same time to minimize the exporters’ risks the stakeholders use trade credit insurance. The paper provides analysis of conceptual background of the trade credit insurance in the world. We analyzed briefly the problems, arising in insurance markets due to asymmetric information, such as adverse selection and moral hazard. Also we discuss the main stages of development of trade credit insurance in countries worldwide. Using comparative and graphical analysis we provide a brief evaluation of the dynamics of claims and recoveries for different forms of trade credit insurance. We found that the claims related to the commercial risk for medium and long trade credits in recent years exceed the recoveries, while with the political risk the reverse trend holds. And we originally consider these findings in terms of information asymmetry in the trade credit insurance differentiated by type of risk.